Length-Weight Relationships and Relative Condition Factor in Priacanthus hamrur (Forsskal) - K.P., Philip; Mathew, Kuruvila (Fishery Technology, 2025)
The length-weight relationship of Priacanthus hamrur was estimated and given by the equations. Males W = 0.00000638 L31133 and Female W = 0.00000811 L3 685. The b value showed significant difference between males and females. The b value computed for female did not show significant variation for the isometric value of 3 whereas in male the departure was found significant. In male and female the Kn value steadily increased up to about 100 mm and remained almost static up to about 150 mm and thereafter showed fluctuation. The seasonal change taking place in Kn value mainly indicate that in P. hamrur it is greatly influenced by feeding intensity rather than the cyclic change taking place in the gonads.